Cumulative history recorded in the depth distribution of radiocesium in sediments deposited on a sandbar. (December 2015) - Tanaka, Kazuya; Kondo, Hiroaki; Sakaguchi, Aya; Takahashi, Yoshio
Abstract: We collected sediments deposited on a sandbar from the surface to 20 cm in depth in the Abukuma River to clarify the history of radiocesium derived from the Fukushima Daiichi Nuclear Power Plant (FDNPP) accident. We analyzed the 137 Cs concentration in the sediments from size-fractioned samples as well as bulk samples. The depth distribution of 137 Cs showed the highest concentration in the deepest sediment layer (18–20 cm) studied, which indicates that sediments with a lower 137 Cs concentration were transported and deposited on sediments having a higher 137 Cs concentration. At the same time, the depth distribution suggests a decrease in radioactivity in provenance areas of the sediments. Analysis of the size-fractioned sediments indicated that the three sediment layers at 4–6 cm, 16–18 cm and 18–20 cm intervals had similar size distribution of 137 Cs and grain size composition although the concentration levels of 137 Cs were different according to their bulk concentrations. The size distribution of 137 Cs also supported the possibility that the decrease in 137 Cs concentration in bulk sediments above 18 cm is due to a decrease in the level of radioactivity in the catchment area. A comparison of the size distribution of 137 Cs between the sediment layers above and below 18 cm suggested that the 137 Cs concentration in the transported fine sediment particles decreased more with time than the 137 Cs concentration in the coarse particles, reflecting the selective transport of the finer particles. The results of this study demonstrated that sediment layers deposited on a sandbar retained the cumulative history of the fluvial transport of radiocesium after the FDNPP accident. Highlights: We investigated the history of 137 Cs recorded in sediments in the Abukuma River. 137 Cs concentration was the highest in the deepest sediment layer studied. The depth distribution suggests a decrease in radioactivity in provenance areas. 137 Cs concentration in fine sediment particles decreased more with time. Sediment layers retained the cumulative history of the fluvial transport of 137 Cs.